Influence of Maternal Glycemic Status (HbA1c) at Delivery and Risk of Hypoglycemia in Infants of Diabetic Mothers - Begum, Mst Nurun Nahar; Hassan, M Quamrul; Nessa, Maherun; Azad, Kishwar (BIRDEM Medical Journal, 2012)
Objective: To examine the influence of maternal HbA1c level at delivery and risk of hypoglycemia in infants of diabetic mothers. Method: This case-control study was done with sixty neonates born to diabetic mothers in BIRDEM hospital. Out of sixty neonates, 30 neonates who developed hypoglycemia during the first 24 hours of age were considered as cases and another 30 neonates who did not develop hypoglycemia during the first 24 hours were considered as controls. Maternal glycemic status was examined by measurement of Glycosylated hemoglobin (HbA1c) and level of <6 % considered good control. Babies were screened for hypoglycemia at birth, then 4, 6, 8, 12, 18 and 24 hours of life. Blood glucose value of less than 2.6 mmol/l was considered as hypoglycemia. Results: Clinical characteristics of newborns and their mothers of cases and controls did not show any significant difference. In majority of cases (73.3%) hypoglycemia was detected by 6 hours of age. Most of babies were asymptomatic (93.3%). Majority of mothers (76.7%) in controls and 46.7% of were in good glycemic controls (HbA1c <6%). The mean HbA1c level of mothers of cases was significantly higher than that of control mothers (6.02 ± 0.98 vs 5.44 ± 0.78; P = 0.014) and significant negative correlation between maternal HbA1c and blood glucose level of neonates ( r=0.422 p= 0.001). Conclusion: There is an association between maternal HbA1c level and neonatal hypoglycemia in infants of diabetic mothers. DOI: http://dx.doi.org/10.3329/birdem.v2i2.12308 (Birdem Med J 2012; 2(2): 84-88)